2016
DOI: 10.1097/pra.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Temperament and Character Inventory to Predict Response to Repetitive Transcranial Magnetic Stimulation for Major Depression

Abstract: Objective . The goal of this study was to investigate the utility of the Temperament and Character Inventory (TCI) in predicting antidepressant response to repetitive transcranial magnetic stimulation (rTMS). Background Although rTMS of the dorsolateral prefrontal cortex (DLPFC) is an established antidepressant treatment, little is known about predictors of response. The TCI measures multiple personality dimensions (harm avoidance, novelty seeking, reward dependence, persistence, self-directedness, self-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Hence, the correlation between HA and HF-rTMS effects in the sgACC reported here, warrants further clinical studies to investigate the possibility of using this personality dimension as a predictor for HF-rTMS driven antidepressant effects. Of note, previous HF-rTMS studies have reported persistence 63 and self-directedness 64 scores of the TCI as good predictors of antidepressant effects. Upon post-hoc analysis, we did not find such correlations between other TCI dimensions and HF-rTMS induced changes in the sgACC and this might be, since our sample consisted of healthy volunteers.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, the correlation between HA and HF-rTMS effects in the sgACC reported here, warrants further clinical studies to investigate the possibility of using this personality dimension as a predictor for HF-rTMS driven antidepressant effects. Of note, previous HF-rTMS studies have reported persistence 63 and self-directedness 64 scores of the TCI as good predictors of antidepressant effects. Upon post-hoc analysis, we did not find such correlations between other TCI dimensions and HF-rTMS induced changes in the sgACC and this might be, since our sample consisted of healthy volunteers.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, De Fruyt et al [14] demonstrated that Conscientiousness and Extraversion (NEO-V) are positively associated with Self-Directedness (TCI), and that Agreeableness and Extraversion (NEO-V) are positively correlated to Cooperativeness (TCI), also one of the three character dimensions of the TCI (the third character dimension of the TCI is Self-transcendence). Regarding temperament dimensions, Siddiqi et al [15] have recently shown that higher Persistence scores predicted antidepressant response to rTMS in a broad range of patients with major depression. With respect to other TCI scales, Singh et al [16] observed in healthy participants after a single HF-rTMS session that Harm Avoidance was related to a decrease in connectivity between the default network model and the subgenual Anterior Cingulate Cortex, a brain area that is assumed to be behind HF-rTMS treatment effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment led to improvements in clinicianassessed mood ratings, self-report emotional scores (including ratings of mood, anger, anxiety, and behavioral dyscontrol), and fluid cognition. Quantitative personality testing showed particularly drastic changes in persistence, a measure of reward-based learning that is related to mOFC-NAcc connectivity (44) and has some predictive value for rTMS response (45). This was accompanied by apparent normalization of connectivity in circuits related to rewardbased learning and reward-motivated behavior, although this is difficult to assess conclusively in a single subject.…”
Section: Discussionmentioning
confidence: 99%